Cancer Network for Welfare Aging (NEWAYS): Strategies for Optimizing the Care of Elderly Patients with Cancer - Pimentel, Francisco Luís; Veríssimo, Manuel; Oliveira, Carlos; Soares, Jorge; Sousa, Gabriela; Martinho da Silva, Paula; Vilaverde Cabral, Manuel; Lopes Ferreira, Pedro (Portuguese Journal Internal Medicine, 2021)
The project NEWAYS − Cancer Network for Welfare Aging aimed to raise national awareness for Geriatric Oncology issue in Portugal. To do so, it set to define strategic courses of action in four preponderant areas in the care of elderly with cancer, in order to foster its optimization and promote the development of Geriatric Oncology policies in Portugal: clinic, economics and health policy, epidemiologic and social investigation and other areas (health literacy, patient-oriented information technologies, ethics, patient advocacy and awareness). After a wide consensus amongst the group of experts who composed the network that leveraged this project, the proposed courses of action are now presented.